SYNERGIZING APPLIED LINGUISTICS FOR EFFECTIVE LANGUAGE TEACHING - Ifana Syahesti (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
In a globalized world, effective language instruction is an imperative need. It must be comprehensive, involving critical thinking, communication skills, and multicultural awareness in addition to linguistic expertise. The combination of applied linguistics and language teaching has led to a revised definition of language education, emphasizing the dynamic relationship between the two fields. The focus of this article is to examine how the principles of applied linguistics can enhance the language teaching.. Using a qualitative methodology, the article delves into the viewpoints of language teachers and the influence it has on the results of language teaching. The findings of this study highlight the potential for more effective and culturally sensitive language education by capitalizing on the synergy between applied linguistics and language teaching. The research underscores the transformative power of applied linguistics, offering a nuanced perspective on how teachers can harness linguistic theories to create engaging, learner-centered, and globally relevant language learning experiences. As language education evolves in a rapidly changing world, the fusion of applied linguistics and teaching practices is reshaping the future of language instruction, making it a more inclusive and effective endeavor for diverse learners seeking to unlock the power of language.